Oxytocin and Borderline Personality Disorder - Bertsch, Katja; Herpertz, Sabine (Behavioral pharmacology of neuropeptides: Oxytocin, 2017)
Borderline personality disorder (BPD) is a prevalent and severe mental disorder with affect dysregulation, impulsivity, and interpersonal dysfunction as its core features. Up to now, six studies have been performed to investigate the role of oxytocin in the pathogenesis of BPD. While a beneficial effect of oxytocin on threat processing and stress responsiveness was found, other studies using an oxytocin challenge design presented with rather heterogeneous results. Future studies have to include a sufficiently large sample of patients, control for gender, and focus on mechanisms known to be related to aversive early life experiences.
Gesehen am 06.06.2018